Angiolupoid sarcoidosis with systemic involvement in an 11-year-old girl. - Thirumalaiswamy, A.; Shah, A.; Kharkar, V. (European Journal of Pediatric Dermatology, 2023)
Sarcoidosis is a chronic granulomatous disease of unknown etiology that can affect many organs, most frequently the lungs, lymph nodes, and eyes; the skin is involved in about a quarter of patients with manifestations of various type. Angiolupoid sarcoidosis is a rare variant of sarcoidosis, even more rare in children and can be associated with multisystem involvement: a case is described in an 11-year-old girl.